Metamaterial Inspired Microstrip Antenna Investigations Using Metascreens - Muhammad Tauseef Asim; Mushtaq Ahmed (International Journal of Antennas and Propagation)
A dual layer periodically patterned metamaterial inspired antenna on a low cost FR4 substrate is designed, simulated, fabricated, and tested. The eigenmode dispersion simulations are performed indicating the left handed metamaterial characteristics and are tunable with substrate permittivity. The same metamaterial unit cell structure is utilized to fabricate a metascreen. This metascreen is applied below the proposed metamaterial antenna and next used as superstrate above a simple patch to study the effects on impedance bandwidth, gain, and radiation patterns. The experimental results of these antennas are very good and closely match with the simulations. More importantly, the resonance for the proposed metamaterial antenna with metascreen occurs at the left handed (LH) eigenfrequency of the metamaterial unit cell structure. The measured −10 dB bandwidths are 14.56% and 22.86% for the metamaterial antenna with single and double metascreens, respectively. The metascreens over the simple patch show adjacent dual band response. The first and second bands have measured −10 dB bandwidths of 9.6% and 16.66%. The simulated peak gain and radiation efficiency are 1.83 dBi and 74%, respectively. The radiation patterns are also very good and could be useful in the UWB wireless applications.